2018
DOI: 10.1039/c7ce01237c
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphs of oxindole as the core structures in bioactive compounds

Abstract: A new polymorph of oxindole (termed as “δ-form”) has been found and characterized by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, in the rest of the solvents [1-propanol (Figure d), 2-propanol (Figure e), DCM (Figure g), EtOAc (Figure i) and acetonitrile (Figure j)], the characteristic peaks at 17° and 26° are very weak whereas other characteristic peaks at 15° and 23° become stronger, which means another polymorph is obtained. After searching the literature, we found that this phenomenon had been reported . There are four polymorphs for 2-oxindole, that is, α, β, γ, and δ.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…However, in the rest of the solvents [1-propanol (Figure d), 2-propanol (Figure e), DCM (Figure g), EtOAc (Figure i) and acetonitrile (Figure j)], the characteristic peaks at 17° and 26° are very weak whereas other characteristic peaks at 15° and 23° become stronger, which means another polymorph is obtained. After searching the literature, we found that this phenomenon had been reported . There are four polymorphs for 2-oxindole, that is, α, β, γ, and δ.…”
Section: Resultsmentioning
confidence: 86%
“…After searching the literature, we found that this phenomenon had been reported. 35 There are four polymorphs for 2-oxindole, that is, α, β, γ, and δ. As Hachuła et al had pointed, 35 the α-form was the most available form and the β-form is the most theoretically stable form.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations